Islamic Education and Environmetal Awareness : Trends and Knowledge Structure ( 2000 - 2025) - Nurul Hayati; Benny Prasetiya; Khoiriyah Khoiriyah; Febry Suprapto (Green Publisher, 2026)
In the past decade, research in Islamic education and human ethics has seen a significant acceleration, marked by increased publications, global collaboration, and strong interdisciplinary integration, especially after the pandemic. This research focuses on developing a framework that integrates Islamic spirituality, social justice, and technological innovations in education. The study employs a bibliometric analysis to map trends, influential authors, and key themes in the integration of Islamic education with environmental awareness. Findings show an epistemological shift toward Transformative Islamic Humanism, a new paradigm that connects Islamic values with contemporary social issues, such as sustainability and justice. This shift is supported by the dominance of Social Sciences and Arts and Humanities in the research, reflecting the growing humanistic orientation in Islamic education. Geographically, Southeast Asia, particularly Indonesia and Malaysia, emerges as a new research hub. The study identifies future research directions, including developing digital ethics in Islamic education, integrating halal values with sustainability, and fostering community empowerment through Islamic boarding schools (pesantren). This research contributes to bridging Islamic education with environmental sustainability goals and offers new avenues for international collaboration. Practically, it supports the development of eco-Islamic curricula and policies that align with the global Sustainable Development Goals (SDGs).